2013
DOI: 10.1089/jop.2012.0193
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive Chitosan–Dextran Sulfate Nanoparticles for Sustained Drug Delivery to the Ocular Surface

Abstract: Cationic and biocompatible mucoadhesive CDNs have been developed for sustained drug delivery to the ocular surface. The CDNs were stable to lysozyme and showed prolonged adherence to the corneal surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…The retention of IND-NLCs on the corneal surface was determined using an experimental setup previously described by Chaiyasan et al [17]. Porcine eyes were obtained from the local slaughterhouse.…”
Section: Ex Vivo Mucoadhesive Studymentioning
confidence: 99%
“…The retention of IND-NLCs on the corneal surface was determined using an experimental setup previously described by Chaiyasan et al [17]. Porcine eyes were obtained from the local slaughterhouse.…”
Section: Ex Vivo Mucoadhesive Studymentioning
confidence: 99%
“…The nanoparticles were stable to lysozymes and showed prolonged adherence to the corneal surface. 157 Several other groups have also developed dendrimer based nanocarrier systems for the treatment of ocular disease. 158 …”
Section: Nanomedicine As An Emerging Therapeutic Approach For Real mentioning
confidence: 99%
“…The subsequent in vitro and in vivo studies demonstrated that these hybrid nanoparticles could slowly release pilocarpine for 24 h to decrease the pupil diameter of rabbits (miosis effect) more effectively than pilocarpine in liposome, gel and eye drop formulations. Hybrid nanoparticles made of chitosan and dextran sulfate with around 400 nm particle size and around 40 mV zeta potential were stable in the presence of lysozyme for at least 4 h and showed at least 60 min prolonged adherence to the ex vivo porcine corneal surface [117]. After topical instillation of mucoadhesive chitosan-dextran sulfate nanoparticles (~400 nm size/+48 mV zeta potential; FITC labelled), the nanoparticles showed prolonged retention on porcine ocular surface for more than 4 h, and could be endocytosed into the ex vivo porcine corneal epithelial cells via clathrin-dependent pathway (Figure 9) [125].…”
Section: Nanoparticles For Drug Delivery To the Anterior Segmentmentioning
confidence: 99%